Canadian International Petroleum Conference 2000
DOI: 10.2118/2000-017
|View full text |Cite
|
Sign up to set email alerts
|

A General Theory of Gas Production in SAGD Operations

Abstract: The small GOR commonly measured in SAGD projects has not previously been adequately explained, and various phenomena such as "microfingering" have been proposed to account for its presence. It is shown that the production of gases can be entirely explained by gases dissolved in the produced fluids at the temperature and pressure conditions of the SAGD steam chamber. Although methane is produced in part via bitumen, there is a significant contribution from methane dissolved in water as well. Other gases, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In another paper 4 , it has been shown theoretically that hydrogen sulphide from aquathermolysis in SAGD is almost entirely produced, and is produced solely via the produced water owing to its solubility at SAGD steam zone temperature. Likewise, carbon dioxide and methane are predicted to be produced via dissolution in water, although for methane a minor contribution via bitumen (i.e.…”
Section: Field Trialsmentioning
confidence: 99%
“…In another paper 4 , it has been shown theoretically that hydrogen sulphide from aquathermolysis in SAGD is almost entirely produced, and is produced solely via the produced water owing to its solubility at SAGD steam zone temperature. Likewise, carbon dioxide and methane are predicted to be produced via dissolution in water, although for methane a minor contribution via bitumen (i.e.…”
Section: Field Trialsmentioning
confidence: 99%
“…The solubility of gas in a liquid is governed by Henry's Law, which may be stated as as is self-evident from inspection of equation (1). In 1989, Japas and Levelt Sengers 2 provided the theoretical basis for observations made at that time and since, that the distribution coefficients for gases in general, for all solvents-gas pairs, declined as the critical point of the solvent was approached.…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, Thimm 1 proposed that gas production in SAGD proceeds via a mechanism whereby gases are dissolved in the produced liquids, and enter the wellbore in that form. No case has been reported so far where it has been necessary to postulate free gas entering the SAGD production well in order to explain the observed GOR and produced gas compositions.…”
Section: Introductionmentioning
confidence: 99%
“…The negative impacts of gas on SAGD operation have also been noticed, but usually considered minor [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Recently, however, theoretical and numerical study had shown that the negative impacts of gas on SAGD could be critical [16].…”
Section: Introductionmentioning
confidence: 99%